Monitoring Corruption: Can Top-Down Monitoring Crowd Out Grassroots Participation? - Gonzalez, Robert; Harvey, Matthew; Tzachrista, Foteini (Economic Development and Cultural Change, 2025)
Empirical evidence on the effectiveness of grassroots monitoring is mixed. This paper proposes a previously unexplored mechanism that may explain this result. We argue that the presence of effective top-down monitoring alternatives can undermine citizen p
Keywords: Grassroots Participation; Micro-Fnance Projects; Village Infrastructure Projects; Corruption